Systematic Literature Review: APPLICATION OF PROBLEM-BASED LEARNING MODELS TO IMPROVE MATHEMATICAL CREATIVE THINKING ABILITIES - Abid, Jauhar Naufan; Waluya, Stevanus Budi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
In 2022, the Program for International Student Assessment (PISA) conducted a global creativity survey, revealing that Indonesian’s mathematical literacy ranks in the low category. To address this issue, enhancing student’s creativity skills in mathematics education is essential. One potential strategy is the application of problem-based learning models. This study aims to re-examine the effectiveness of problem-based learning in fostering students’ mathematical creative thinking skills. The research employs a systematic literature review approach, with data gathered from articles and research journals related to mathematical creative thinking and problem-based learning. The data sources are limited to studies published between 2020 and 2024.